The Effect of Risk Based Audit, Internal Control System and Organizational Commitment to Fraud Prevention With Ethical Considerations as Moderating Variables: Empirical Study on State-Owned Enterprises in Palembang City - Jihan Aviva (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The formulation in this study is how the influence of Risk Based Audit, Internal Control System, and Organizational Commitment to Fraud Prevention with Ethical Considerations as Moderating Variables. The aim is to determine the effect of Risk Based Audit, Internal Control System, and Organizational Commitment to Fraud Prevention with Ethical Considerations as Moderating Variables. This research uses associative research type. The place of research was carried out in BUMN in the city of Palembang. The data used is primary data. Data collection techniques are interviews and questionnaires. The sampling method used purposive sampling. The analytical method used is multiple linear regression analysis and moderate regression analysis. Together, Risk Based Audit, Internal Control System, and Organizational Commitment have an effect on Fraud Prevention. These results partially indicate that the Internal Control System has an effect on fraud prevention, Risk Based Audit and Organizational Commitment have no effect on Fraud Prevention. And in moderation Ethical Consideration is a Homologiser of Internal Control System Moderation on Fraud Prevention, Ethical Consideration is a Predictor of Risk Based Audit Moderation and Organizational Commitment to Fraud Prevention. Keywords: Risk Based Audit, System, Commitment, Consideration, Prevention